Comparing the Reverse Trendelenburg and Horizontal Position for Endoscopic Sinus Surgery: A Randomized Controlled Trial. Issue 2 (31st October 2012) - Hathorn, Iain F.; Habib, Al‐Rahim R.; Manji, Jamil; Javer, Amin R.
Abstract : Objective: To determine whether the 15‐degree reverse Trendelenburg position (RTP) during functional endoscopic sinus surgery improves endoscopic field of view and reduces intraoperative blood loss when compared with the horizontal position (HP). Study Design: A prospective, randomized controlled trial. Setting: St Paul's Sinus Centre, Vancouver, Canada. Subjects: Patients with chronic rhinosinusitis (CRS), with or without nasal polyposis, receiving functional endoscopic sinus surgery were included. Patients were excluded if they had severe or uncontrolled hypertension and cardiovascular disease, continued use of anticoagulants, impaired coagulation, or a sinonasal tumor. Methods: Sixty‐four patients with CRS undergoing functional endoscopic sinus surgery (FESS) were randomized to either 15‐degree RTP (experimental arm) or HP (control arm) from October 2011 to February 2012. Boezaart endoscopic field‐of‐view grading system was the primary outcome measure. Lund‐Mackay computed tomography (CT) score, total blood loss, blood loss per minute, mean arterial pressure, heart rate, anesthetic technique, and surgery time were also recorded. Results: There was a significant difference in mean Boezaart scoring between RTP and HP: 1.66 vs 2.33 ( P <. 001), with RTP producing a better endoscopic field of view. There was also a lower total blood loss and blood loss per minute with RTP ( P =. 01, P =. 03). There was no significant difference in disease severity ( P >. 05), time of surgery ( P >. 05), or mean arterial pressure ( P >. 05) between the 2 surgical positions. Conclusion: The 15‐degree RTP improves the endoscopic field of view and reduces blood loss during FESS. We would therefore recommend its use.